2012
DOI: 10.1007/s11010-011-1222-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog pathway is essential for neuroblastoma cell proliferation and tumor growth

Abstract: Accumulated evidence suggests a major role for the activation of the Sonic Hedgehog (SHH) signaling pathway in the development of neural crest stem cells that give rise to the sympathetic nervous system. We therefore investigated the involvement of SHH signaling in the pathogenesis of neuroblastoma (NB), a common childhood malignant tumor of the sympathetic nervous system. Inhibition of SHH signaling by cyclopamine induced apoptosis and blocked proliferation in all major types of NB cells, and abrogated the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…To date, a relationship between the SHH and autophagy pathways has not been reported, although it has been shown that there are cancers that are sensitive to both pathways, as for instance neuroblastoma (Mao et al, 2009;Mohan et al, 2011;Xu et al, 2012).…”
Section: A New Paradigm For Shh/gli Therapeutic Action: In-hibition Omentioning
confidence: 99%
“…To date, a relationship between the SHH and autophagy pathways has not been reported, although it has been shown that there are cancers that are sensitive to both pathways, as for instance neuroblastoma (Mao et al, 2009;Mohan et al, 2011;Xu et al, 2012).…”
Section: A New Paradigm For Shh/gli Therapeutic Action: In-hibition Omentioning
confidence: 99%
“…5 μg total RNA in a volume of 20 μl was reversely transcribed by using SuperScript III reagent (Life Technologies) and the oligo-(deoxythymidine) primers followed by incubation at 42°C for 1 h. After termination of cDNA synthesis, each reaction mixture was diluted with 80 μl Tris-EDTA buffer. Messenger RNA levels of target genes were determined by quantitative RT-PCR as described previously [16,22]. The relative amounts of the mRNA levels of the target genes from triplicates were normalized to the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and β-actin levels, respectively, and the relative difference in mRNA levels was calculated by 2 − ΔΔCt method.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Transient transfection and dual-luciferase assay were performed as previously described [15,16]. Briefly, after plated in 24-well plates for 24 h, SH-SY5Y cells in the serum-free medium were transfected with 2 μg GLI-luciferase reporter construct and 0.02 μg pRL-null expressing Renilla luciferase by using Lipofectamine 2000 reagent (Life Technologies) for 6 h. In some cases, the cells were co-transfected with RET-or AKT*-expressing plasmid at 0.2 μg each.…”
Section: Transient Transfection and Dual-luciferase Assaymentioning
confidence: 99%
See 2 more Smart Citations